Pengaruh Kegagalan Fungsional, Kegagalan Sistem, Kegagalan Informasi dan Kegagalan Layanan Terhadap Penggunaan M-Banking Serta Kaitannya dengan Kepuasan Nasabah BCA Mobile di Indonesia - Intan Ayu Permatasari; Fitriani Nur Utami (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The rapid development of technology is the main driver of the emergence of digital-based products and services. One of the technology-based banking service products is mobile banking. In Indonesia, the mobile banking that has the most users is BCA Mobile. However, with the largest number of users, the quality of BCA Mobile itself still often complained about by its users. The purpose of this study was to determine how much influence functional failure, system failure, information failure, and service failure have on the use of BCA Mobile and its relationship with user satisfaction. The method used is quantitative method. The sampling technique uses SRS or simple random sampling with a sample size of 400 respondents who are BCA Mobile users in Indonesia. Data collection using a questionnaire distributed via Google Form. The data analysis technique used is SEM - PLS with SmartPLS 4.0 software. The results of this study indicate that functional failure, information failure, and service failure have no effect on the use of BCA Mobile, while system failure has a negative and significant effect on the use of BCA Mobile, and the use of BCA Mobil affects user satisfaction.